Economics of monetary union - Grauwe, Paul de. (Oxford ; New York : Oxford University Press, 2007)
EMU as a classic text analyzes the costs and benefits associated with having one currency as well as the practical workings and current issues involved with the euro. In the first part, the author considers the implications of joining a monetary union through an economic cost & benefit analysis. The second part looks at the reality of monetary unions by analyzing Europe's experience, how it was designed to conduct a single monetary policy.
Includes bibliographical references and index.
nmn 10/05/13
Loans
Keywords: Monetary unions; Monetary policy; European monetary system (organisation); European Union countries